Argyrophilic Fibers of Intravascular Threadlike Structures in Rat - Byung-Cheon Lee; Tae Jeong Nam; Hyeon-Min Johng; Eun Sung Park; Ku Youn Baik; Baeckkyoung Sung; Kyung-Soon Soh; Yeo Sung Yoon; Kwang-Sup Soh (Korean Pharmacopuncture Institute, 2008)
Objective : We took intravascular threadlike structures from rat aortas to investigate their histological characteristics consistent with the intravascular Bonghan duct. Methods : Gomori's silver impregnation method, in addition to routine hematoxylin and eosin staining, was applied to demonstrate the characteristic feature of the intravascular threadlike structures. Results : These two staining methods clearly showed that the intravascular threadlike structures had unique features of argyrophilic reticular fibers and heavily stained oval or rod-shaped nuclei in them. Conclusion : The results are strong evidences for identifying threadlike structure as the intravascular Bonghan duct.